Determinação multirresíduo de agrotóxicos em água empregando SPE e UHPLC-MS/MS - Avellar, Állisson Alberto da Silva (2020)
The presence of organic pollutants in water resources is a major concern. The most commonly reported of these pollutants are generated by domestic, agricultural and industrial activities. Organic pollutants produce a wide range of toxic effects in animals and humans, including on reproductive, nervous and immune systems, in addition to damage to the environment. However, their danger is not limited to their toxicity, but also stems from their persistence, mobility and ability to accumulate in organisms, water, soil and air. Although the concentration of these pollutants in water is usually very low, but they can persists on water and when consumed, can compromise human health. Therefore, an adequate sample preparation as well as a development of reliable analytical method to monitor these contaminants in water samples are required. Thus, the aim of this work was to develop and validate a multiresidue method for determination of 94 pesticide residues in water samples using solid phase extraction (SPE) and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). Different sorbents, solvents and elution volumes were evaluated. The best results were obtained using the SPE cartridge Oasis® HLB 60 mg/3 mL and acetonitrile acidified with 1% (v/v) acetic acid as elution solvent. Analytical curves were linear between 1.0 and 20.0 μg L-¹, with r² values greater than 0.99 for all compounds. The limits of quantification and detection of the method were 0.04 to 0.40 μg L-¹ and 0.01 to 0.12 μg L-¹, respectively. To evaluate accuracy and precision, “blank” samples were spiked at 0.04, 0.10, 0.20 and 0.40 μg L-¹. The method showed good precision, with RSD values below to 20% and good accuracy, with recoveries between 70 and 120%. The validated method was applied to 12 samples of water of different characteristics (river, artesian well, dam and treated water) and the analyzed samples presented residues of 2,4-D, carbendazim, chlorpyrifos, diuron, thiamethoxam and tricyclazole. The results show this sample preparation presented great versatility and allowed good recovery of different classes of analytes for analysis of pesticide residues in drinking water and could be applied in pesticide routine analyzes.